Preparation method of temperature-sensitive dual-network hydrogel for salt ion adsorption

By preparing a temperature-sensitive dual network hydrogel for salt ion adsorption, the problems of high energy consumption and high cost in the prior art are solved by using electrostatic action and temperature response, and the efficient adsorption and desalting effects of salt ions under low temperature conditions are achieved.

CN119735764AInactive Publication Date: 2025-04-01TIANJIN POLYTECHNIC UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510018958.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has high energy consumption for heat treatment, high membrane technology cost and short life when treating bitter and salty water. Especially under high salinity conditions, efficiency is limited, and it is urgently necessary to develop efficient and low-cost desalination technology.

Method used

A temperature-sensitive dual network hydrogel prepared with N-isopropyl acrylamide and acrylic acid as the main materials is used to achieve efficient adsorption of salt ions and dynamic regulation of internal hydrogen ion concentration through the electrostatic effect of carboxyl groups on acrylic acid and the temperature responsiveness of N-isopropyl acrylamide.

Benefits of technology

It realizes efficient adsorption of salt ions under low temperature conditions, expands the pH gradient inside and outside the hydrogel, improves the adsorption efficiency of salt ions, and provides a low-cost and low-energy-consuming desalination solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735764A_ABST
    Figure CN119735764A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of temperature-sensitive dual-network hydrogel for salt ion adsorption, the hydrogel is mainly composed of N-isopropylacrylamide and acrylic acid, and the acrylic acid containing rich carboxyl significantly enhances the ability of the hydrogel to adsorb salt ions through electrostatic interaction. Meanwhile, the number of available adsorption sites is increased by adding the modified graphite powder, so that the ion adsorption is further enhanced. Due to the addition of N-isopropylacrylamide, the reaction to the temperature change is relatively sensitive. During heating, the temperature-sensitive double-network hydrogel can promote water release and physical shrinkage and improve the internal hydrogen ion concentration, so that the internal and external pH value difference of the hydrogel is enlarged, efficient adsorption of metal salt ions and water neutralization are achieved, and an effective and environment-friendly solution is provided for obtaining fresh water and repairing saline-alkali soil; and sustainable development of global water resource management is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a temperature-sensitive double-network hydrogel for salt ion adsorption, which is specifically applied to saline-alkali land, brackish water restoration and other related fields. Background Art

[0002] The global water shortage problem is becoming increasingly serious. Nearly 25% of the population faces severe water shortage, especially in developing countries and arid areas. Due to poor land management, backward irrigation technology and pollution, a large amount of groundwater is converted into brackish water that is not suitable for drinking, agricultural irrigation or industrial applications, exacerbating the water crisis. At present, brackish water treatment technologies are mainly based on thermal treatment (such as multi-effect distillation) and membrane separation (such as reverse osmosis), but thermal treatment has high energy consumption, and membrane technology is expensive and has a short lifespan, especially under high salinity conditions. Therefore, it is urgent to develop efficient and low-cost desalination technology to meet this challenge. In this context, hydrogel has become a very promising water purification material due to its unique physicochemical properties. Hydrogel has an adjustable network structure and functional groups, which can efficiently remove heavy metals, organic pollutants and salt ions. At the same time, its eco-friendliness and biodegradability reduce the impact on the environment and meet the goal of sustainable development.

[0003] For example, Chinese patent CN 118387965 A discloses a "method for purifying brackish water by modified aerogel". The purification method comprises adding acid-modified aerogel to brackish water and stirring to form a first solid-liquid mixture, performing solid-liquid separation on the first solid-liquid mixture to obtain primary purified brackish water, adding alkali-modified aerogel to the primary purified brackish water and stirring to form a second solid-liquid mixture, performing solid-liquid separation on the second solid-liquid mixture to complete the purification of brackish water. The method utilizes the characteristics of high specific surface area and high porosity of modified aerogel to improve the adsorption capacity. For example, Chinese patent CN 220485407 U discloses "a brackish water two-stage nanofiltration device". The first-stage nanofiltration device and the second-stage nanofiltration device both include a concentrated water chamber and a clear water chamber separated by a nanofiltration membrane. The purification effect of brackish water is improved by two-stage filtration.

[0004] Therefore, a thermosensitive double network hydrogel for salt ion adsorption was prepared with N-isopropylacrylamide and acrylic acid as the main materials. Among them, the rich carboxyl groups of acrylic acid can provide the adsorption capacity of salt ions through electrostatic action, while N-isopropylacrylamide gives the hydrogel the ability to expand and shrink under temperature induction. This thermosensitive behavior can dynamically adjust the internal hydrogen ion concentration and form a pH gradient between the gel core and the external solution, thereby further improving the adsorption efficiency of salt ions. Therefore, the development of thermosensitive double network hydrogels provides new possibilities for achieving efficient adsorption and alkaline neutralization of salt ions under low temperature conditions. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a temperature-sensitive double-network hydrogel for salt ion adsorption. With N-isopropylacrylamide and acrylic acid as the main materials, the electrostatic effect of the carboxyl group on acrylic acid is used to achieve efficient adsorption of salt ions. At the same time, through the temperature responsiveness of N-isopropylacrylamide, the hydrogel can dynamically adjust the internal hydrogen ion concentration, form a pH gradient between the gel and the external solution, and further enhance the adsorption efficiency. The present invention provides a new solution for efficiently removing salt ions from brackish water under low temperature conditions.

[0006] The technical solution of the present invention is:

[0007] Step 1: preparing modified graphite powder. First, at high temperature, the graphite powder is hydrophilically modified using a tannic acid solution, and the modified graphite powder is obtained after a period of reaction;

[0008] Step 2: preparing a precursor solution, adding modified graphite powder in a certain proportion to a mixed solution consisting of N-isopropylacrylamide, methylenebisacrylamide and potassium persulfate to prepare a precursor solution;

[0009] Step 3, preparing the first network of the hydrogel, adding the modified graphite powder to the precursor solution, reacting it fully for a period of time at a certain reaction temperature, and then standing at room temperature for a period of time to form a first network hydrogel with a stable structure;

[0010] Step 4: preparing a thermosensitive double network hydrogel, immersing the first network hydrogel in a mixed solution of acrylic acid and potassium persulfate, and after immersion for a period of time, forming a second network hydrogel in the first network by a low-temperature polymerization method, and finally obtaining a thermosensitive double network hydrogel for salt ion adsorption;

[0011] Furthermore, the high temperature condition in step 1 is 60° C., the concentration of the tannic acid solution is 0.2%, the solvent is deionized water, the mass of the graphite powder is 0.5 g, and the reaction time is 8 h;

[0012] Furthermore, in step 2, the mass concentration of N-isopropylacrylamide is 14%, the mass concentration of methylenebisacrylamide is 1%, the mass concentration of potassium persulfate is 1%, and the amount of modified graphite powder added is 3 mg / mL;

[0013] Furthermore, in step 3, the reaction temperature is 70°C, the reaction time is 25 min, and the standing time at room temperature is 48 h;

[0014] Furthermore, in step 4, the mixed solution of acrylic acid and potassium persulfate has a mass concentration of 14% acrylic acid and a mass concentration of 1% potassium persulfate, an immersion time of 72 hours, and a low-temperature polymerization temperature of 2-5°C. The molar ratio of the monomer N-isopropylacrylamide of the first network hydrogel to the monomer acrylic acid of the second network hydrogel is 7:3.

[0015] The advantages of the present invention are:

[0016] The hydrogel has significant temperature sensitivity. At relatively low temperature conditions (35°C), it can quickly release water and physically shrink, increasing the hydrogen ion concentration inside the hydrogel, thereby expanding the pH gradient inside and outside the hydrogel and achieving efficient adsorption of salt ions.

[0017] The hydrogel is added with modified graphite powder treated with tannic acid for hydrophilic modification. The introduction of hydrophilic groups strengthens the interaction between the modified graphite powder and water molecules, thereby improving its dispersibility. The uniformly distributed modified graphite powder further improves the adsorption capacity of the temperature-sensitive double network hydrogel for salt ions.

[0018] The hydrogel and salt ions are effectively combined through significant electrostatic interactions, which can firmly fix the salt ions on the adsorption sites. Under high salinity conditions, the hydrogel shows excellent adaptability and selectivity for sodium ions in competitive adsorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them,

[0020] Figure 1 This is the SEM image of the internal cross section of the thermosensitive double network hydrogel;

[0021] Figure 2 is the effect of monomer concentration on the adsorption properties of hydrogel;

[0022] Figure 3 The effect of the amount of modified graphite powder added on the adsorption properties of hydrogel;

[0023] Figure 4 is the relationship between the amount of sodium ions adsorbed by the hydrogel and the initial concentration of sodium ions in the solution;

[0024] Figure 5 is the relationship between the amount of magnesium ions adsorbed by the hydrogel and the initial concentration of magnesium ions in the solution;

[0025] Figure 6 Comparison of the removal rates of sodium and magnesium ions by hydrogels under different initial concentrations. DETAILED DESCRIPTION

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the technical solution of the present invention is further described below in conjunction with the accompanying drawings, embodiments and comparative examples. However, the present invention is not limited to the embodiments listed, but also includes any other known changes within the scope of the rights claimed by the present invention.

[0027] First, the "embodiment 1" referred to herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. Secondly, the present invention is described in detail using a structural schematic diagram, etc. When describing the embodiment of the present invention in detail, for the sake of convenience, the schematic diagram will not be partially enlarged according to the general scale, and the schematic diagram is only an example, which should not limit the scope of protection of the present invention. In addition, in actual production, a three-dimensional space of length, width and depth should be included.

[0028] In addition, the abbreviations mentioned in the present invention are fixed abbreviations in the field, and some of the abbreviations are explained as follows: SEM: scanning electron image.

[0029] Embodiment 1

[0030] This embodiment prepares a temperature-sensitive double network hydrogel for salt ion adsorption according to the following steps;

[0031] The first step is to prepare modified graphite powder;

[0032] Firstly, the graphite powder was hydrophilically modified by using tannic acid solution at 60°C, and the modified graphite powder was obtained after reacting for 8 hours.

[0033] Step 2: prepare the precursor solution;

[0034] Dissolve 14% N-isopropylacrylamide, 1% methylenebisacrylamide and 1% potassium persulfate in deionized water, and add modified graphite powder at a specification of 3 mg / mL to prepare a precursor solution;

[0035] Step 3: Prepare the first network of hydrogel;

[0036] After adding the modified graphite powder into the precursor solution, the reaction was carried out at 70°C for 25 min and then allowed to stand at room temperature for 48 h to form the first network hydrogel with a stable structure;

[0037] Step 4: preparing a thermosensitive double network hydrogel;

[0038] The first network hydrogel is immersed in a mixed solution of acrylic acid with a mass concentration of 14% and potassium persulfate with a mass concentration of 1%, and immersed at a low temperature of 2-5°C for 72 hours, and a second network hydrogel is formed in the first network by a low temperature polymerization method, and finally a temperature-sensitive double network hydrogel for salt ion adsorption is obtained;

[0039] Step 5: Test the adsorption performance of the hydrogel;

[0040] The prepared thermosensitive double network hydrogel was placed in a brackish water solution and its adsorption performance was tested at 35°C.

[0041] For the surface SEM image of the thermosensitive double network hydrogel prepared in this example, please refer to Figure 1 .

[0042] Embodiment 2

[0043] This embodiment prepares thermosensitive double network hydrogels with different monomer concentrations according to the following steps;

[0044] The first step is to prepare a precursor solution;

[0045] Dissolving 13% N-isopropylacrylamide, 1% methylenebisacrylamide and 1% potassium persulfate in deionized water to prepare a precursor solution;

[0046] Step 2: Prepare the first network of thermosensitive hydrogel;

[0047] The precursor solution was reacted at 70°C for 25 min and allowed to stand at room temperature for 48 h to form a first network hydrogel with a stable structure;

[0048] Step 3: Prepare thermosensitive double network hydrogel;

[0049] The first network hydrogel is immersed in a mixed solution of acrylic acid with a mass concentration of 13% and potassium persulfate with a mass concentration of 1%, and immersed at a low temperature of 2-5°C for 72 hours, and a second network hydrogel is formed in the first network by a low temperature polymerization method, and finally a temperature-sensitive double network hydrogel for salt ion adsorption is obtained;

[0050] Step 4: Test the adsorption performance of the hydrogel;

[0051] The prepared thermosensitive double network hydrogel was placed in a brackish water solution and its adsorption performance was tested at 35°C.

[0052] Embodiment 3

[0053] This embodiment prepares thermosensitive double network hydrogels with different monomer concentrations according to the following steps;

[0054] The first step is to prepare a precursor solution;

[0055] Dissolving 14% N-isopropylacrylamide, 1% methylenebisacrylamide and 1% potassium persulfate in deionized water to prepare a precursor solution;

[0056] Step 2: Prepare the first network of hydrogel;

[0057] The precursor solution was reacted at 70°C for 25 min and allowed to stand at room temperature for 48 h to form a first network hydrogel with a stable structure;

[0058] Step 3: Prepare thermosensitive double network hydrogel;

[0059] The first network hydrogel was immersed in a mixed solution of acrylic acid with a mass concentration of 14% and potassium persulfate with a mass concentration of 1%, and immersed at a low temperature of 2-5°C for 72 hours, and a second network hydrogel was formed in the first network by a low temperature polymerization method, and finally a temperature-sensitive double network hydrogel for salt ion adsorption was obtained;

[0060] Step 4: Test the adsorption performance of the hydrogel;

[0061] The prepared thermosensitive double network hydrogel was placed in a brackish water solution and its adsorption performance was tested at 35°C.

[0062] Embodiment 4

[0063] In this embodiment, the thermosensitive double network hydrogels with different monomer concentrations are prepared according to the following steps;

[0064] The first step is to prepare a precursor solution;

[0065] Dissolving 15% N.isopropylacrylamide, 1% methylenebisacrylamide and 1% potassium persulfate in deionized water to prepare a precursor solution;

[0066] Step 2: Prepare the first network of hydrogel;

[0067] The precursor solution was reacted at 70°C for 25 min and allowed to stand at room temperature for 48 h to form a first network hydrogel with a stable structure;

[0068] Step 3: Prepare thermosensitive double network hydrogel;

[0069] The first network hydrogel is immersed in a mixed solution of acrylic acid with a mass concentration of 15% and potassium persulfate with a mass concentration of 1%, and immersed at a low temperature of 2-5°C for 72 hours, and a second network hydrogel is formed in the first network by a low temperature polymerization method, and finally a temperature-sensitive double network hydrogel for salt ion adsorption is obtained;

[0070] Step 4: Test the adsorption performance of the hydrogel;

[0071] The prepared thermosensitive double network hydrogel was placed in a brackish water solution and its adsorption performance was tested at 35°C.

[0072] Embodiment 5

[0073] In this embodiment, the thermosensitive double network hydrogels with different monomer concentrations are prepared according to the following steps;

[0074] The first step is to prepare a precursor solution;

[0075] Dissolving 16% N-isopropylacrylamide, 1% methylenebisacrylamide and 1% potassium persulfate in deionized water to prepare a precursor solution;

[0076] Step 2: Prepare the first network of hydrogel;

[0077] The precursor solution was reacted at 70°C for 25 min and allowed to stand at room temperature for 48 h to form a first network hydrogel with a stable structure;

[0078] Step 3: Prepare thermosensitive double network hydrogel;

[0079] The first network hydrogel is immersed in a mixed solution of acrylic acid with a mass concentration of 16% and potassium persulfate with a mass concentration of 1%, and immersed at a low temperature of 2-5°C for 72 hours, and a second network hydrogel is formed in the first network by a low temperature polymerization method, and finally a temperature-sensitive double network hydrogel for salt ion adsorption is obtained;

[0080] Step 4: Test the adsorption performance of the hydrogel;

[0081] The prepared thermosensitive double network hydrogel was placed in a brackish water solution and its adsorption performance was tested at 35°C.

[0082] Through comprehensive comparative examples, it can be obtained that when the mass concentration of the monomer increases from 13% to 16%, the adsorption amount per gram of hydrogel also increases from 1.48g to 1.77g. This enhancement is mainly due to the increase in monomer concentration, especially the addition of acrylic acid, which introduces more carboxyl groups and increases the number of available adsorption sites. However, when the mass concentration of the monomer is further increased to 15% and 16%, the adsorption amount per gram of hydrogel decreases to 1.67g and 1.52g, respectively. This reduction is attributed to the increase in cross-linking density, which leads to crowding of the interchain space inside the polymer, and the reduction of channels for adsorption sites, and destroys the pore structure of the thermosensitive double network hydrogel, thereby limiting the diffusion of salt ions. For the specific effects of different monomer concentrations on the adsorption properties of hydrogels, please refer to Figure 2 .

[0083] Comparative Example 1

[0084] In this comparative example, the temperature-sensitive double network hydrogels with different amounts of modified graphite powder added were prepared according to the following steps;

[0085] The first step is to prepare modified graphite powder;

[0086] Firstly, the graphite powder was hydrophilically modified by using tannic acid solution at 60°C, and the modified graphite powder was washed and dried after reacting for 8 hours.

[0087] Step 2: prepare the precursor solution;

[0088] Dissolve 14% N-isopropylacrylamide, 1% methylenebisacrylamide and 1% potassium persulfate in deionized water, and add modified graphite powder at a specification of 1 mg / mL to prepare a precursor solution;

[0089] Step 3: Prepare the first network of hydrogel;

[0090] After adding the modified graphite powder into the precursor solution, the reaction was carried out at 70°C for 25 min and then allowed to stand at room temperature for 48 h to form the first network hydrogel with a stable structure;

[0091] Step 4: preparing a thermosensitive double network hydrogel;

[0092] The first network hydrogel was immersed in a mixed solution of acrylic acid with a mass concentration of 14% and potassium persulfate with a mass concentration of 1%, and immersed at a low temperature of 2-5°C for 72 hours, and a second network hydrogel was formed in the first network by a low temperature polymerization method, and finally a temperature-sensitive double network hydrogel for salt ion adsorption was obtained;

[0093] Step 5: Test the adsorption performance of the hydrogel;

[0094] The prepared thermosensitive double network hydrogel was placed in a brackish water solution and its adsorption performance was tested at 35°C.

[0095] Comparative Example 2

[0096] The first step is to prepare modified graphite powder;

[0097] Firstly, the graphite powder was hydrophilically modified by using tannic acid solution at 60°C, and the modified graphite powder was washed and dried after reacting for 8 hours.

[0098] Step 2: prepare the precursor solution;

[0099] Dissolve 14% N-isopropylacrylamide, 1% methylenebisacrylamide and 1% potassium persulfate in deionized water, add modified graphite powder at a concentration of 2 mg / mL to prepare a precursor solution;

[0100] Step 3: Prepare the first network of hydrogel;

[0101] After adding the modified graphite powder into the precursor solution, the reaction was carried out at 70°C for 25 min and then allowed to stand at room temperature for 48 h to form the first network hydrogel with a stable structure;

[0102] Step 4: preparing a thermosensitive double network hydrogel;

[0103] The first network hydrogel is immersed in a mixed solution of acrylic acid with a mass concentration of 14% and potassium persulfate with a mass concentration of 1%, and immersed at a low temperature of 2-5°C for 72 hours, and a second network hydrogel is formed in the first network by a low temperature polymerization method, and finally a temperature-sensitive double network hydrogel for salt ion adsorption is obtained;

[0104] Step 5: Test the adsorption performance of the hydrogel;

[0105] The prepared thermosensitive double network hydrogel was placed in a brackish water solution and its adsorption performance was tested at 35°C.

[0106] Comparative Example 3

[0107] The first step is to prepare modified graphite powder;

[0108] Firstly, the graphite powder was hydrophilically modified by using tannic acid solution at 60°C, and the modified graphite powder was washed and dried after reacting for 8 hours.

[0109] Step 2: prepare the precursor solution;

[0110] Dissolve 14% N-isopropylacrylamide, 1% methylenebisacrylamide and 1% potassium persulfate in deionized water, and add modified graphite powder at a specification of 4 mg / mL to prepare a precursor solution;

[0111] Step 3: Prepare the first network of hydrogel;

[0112] After adding the modified graphite powder into the precursor solution, the reaction was carried out at 70°C for 25 min and then allowed to stand at room temperature for 48 h to form the first network hydrogel with a stable structure;

[0113] Step 4: preparing a thermosensitive double network hydrogel;

[0114] The first network hydrogel is immersed in a mixed solution of acrylic acid with a mass concentration of 14% and potassium persulfate with a mass concentration of 1%, and immersed at a low temperature of 2-5°C for 72 hours, and a second network hydrogel is formed in the first network by a low temperature polymerization method, and finally a temperature-sensitive double network hydrogel for salt ion adsorption is obtained;

[0115] Step 5: Test the adsorption performance of the hydrogel;

[0116] The prepared thermosensitive double network hydrogel was placed in a brackish water solution and its adsorption performance was tested at 35°C.

[0117] Comparative Example 4

[0118] The first step is to prepare modified graphite powder;

[0119] Firstly, the graphite powder was hydrophilically modified by using tannic acid solution at 60°C, and the modified graphite powder was washed and dried after reacting for 8 hours.

[0120] Step 2: prepare the precursor solution;

[0121] Dissolve 14% N-isopropylacrylamide, 1% methylenebisacrylamide and 1% potassium persulfate in deionized water, and add modified graphite powder at a specification of 5 mg / mL to prepare a precursor solution;

[0122] Step 3: Prepare the first network of hydrogel;

[0123] After adding the modified graphite powder into the precursor solution, the reaction was carried out at 70°C for 25 min and then allowed to stand at room temperature for 48 h to form the first network hydrogel with a stable structure;

[0124] Step 4: preparing a thermosensitive double network hydrogel;

[0125] The first network hydrogel is immersed in a mixed solution of acrylic acid with a mass concentration of 14% and potassium persulfate with a mass concentration of 1%, and immersed at a low temperature of 2-5°C for 72 hours, and a second network hydrogel is formed in the first network by a low temperature polymerization method, and finally a temperature-sensitive double network hydrogel for salt ion adsorption is obtained;

[0126] Step 5: Test the adsorption performance of the hydrogel;

[0127] The prepared thermosensitive double network hydrogel was placed in a brackish water solution and its adsorption performance was tested at 35°C.

[0128] By comprehensively comparing Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, it can be obtained that the addition of modified graphite powder significantly enhances the adsorption capacity of the thermosensitive double network hydrogel for sodium ions. When the addition amount of modified graphite powder is 3 mg / mL, the peak adsorption amount of the hydrogel is nearly 3 times that of the hydrogel without modified graphite powder. The addition of modified graphite powder increases the number of available adsorption sites, thereby enhancing ion adsorption. When the amount of modified graphite powder exceeds 3 mg / mL, the adsorption amount decreases. This reduction may be due to the polymerization and aggregation of modified graphite powder particles at higher concentrations, thereby affecting the accessibility of certain adsorption sites. In addition, the increase in the concentration of modified graphite powder hinders the pore structure of the hydrogel, further reducing the adsorption capacity of the modified graphite powder.

[0129] This study developed a new type of thermosensitive double network hydrogel that is very sensitive to temperature changes. When heated, the thermosensitive double network hydrogel can promote water release and physical contraction, increase the internal hydrogen ion concentration, thereby expanding the pH gradient inside and outside the hydrogel, achieving efficient adsorption of salt ions, making a large amount of brackish water an important resource for alleviating water shortages after treatment, providing an effective and environmentally friendly solution for obtaining fresh water and energy, and promoting the sustainable development of global water resources management.

[0130] It should be noted that the above embodiments and comparative examples are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a temperature-sensitive double network hydrogel for salt ion adsorption, characterized in that: The method comprises the following steps: firstly, under high temperature conditions, graphite powder is hydrophilically modified by using a tannic acid solution, and modified graphite powder is obtained after a reaction period; then, the modified graphite powder is added into a mixed solution composed of N-isopropyl acrylamide, methylenebisacrylamide and potassium persulfate in a certain proportion, and after fully reacting for a period of time at a certain reaction temperature, the modified graphite powder is allowed to stand for a period of time at room temperature to form a first network hydrogel with a stable structure; then, the modified graphite powder is immersed in a mixed solution of acrylic acid and potassium persulfate, and after immersion for a period of time, a second network hydrogel is formed in the first network by a low-temperature polymerization method, and finally a temperature-sensitive double network hydrogel for salt ion adsorption is obtained.

2. The method for preparing a temperature-sensitive double network hydrogel for salt ion adsorption according to claim 1, characterized in that: The high temperature condition is 30-150° C., the concentration of the tannic acid solution is 0.1-5%, the solvent is deionized water, the mass of the graphite powder is 0.1-10 g, and the reaction time is 6-18 h.

3. The method for preparing a temperature-sensitive double network hydrogel for salt ion adsorption according to claim 1, characterized in that: In the mixed solution composed of N-isopropylacrylamide, methylenebisacrylamide and potassium persulfate, the mass concentration of N-isopropylacrylamide is 5-20%, the mass concentration of methylenebisacrylamide is 0.1-5%, the mass concentration of potassium persulfate is 0.1-5%, the added amount of modified graphite powder is 0-30 mg / mL, the reaction temperature of the first network hydrogel formation is 40-100°C, the reaction time is 15-60 min, and the standing time at room temperature is 12-72 h.

4. The method for preparing a temperature-sensitive double network hydrogel for salt ion adsorption according to claim 1, characterized in that: In the mixed solution of acrylic acid and potassium persulfate, the mass concentration of acrylic acid is 5-20%, the mass concentration of potassium persulfate is 0.1-5%, the immersion time is 24-96 hours, and the low-temperature polymerization temperature is 0-10°C.

5. The method for preparing a temperature-sensitive double network hydrogel for salt ion adsorption according to claim 1, characterized in that: The molar ratio of the monomer N-isopropylacrylamide of the first network hydrogel to the monomer acrylic acid of the second network hydrogel is 9:1-1:

9.

6. A temperature-sensitive double network hydrogel for salt ion adsorption prepared by the preparation method according to any one of claims 1 to 5, characterized in that: It is specifically used in saline-alkali land, brackish water restoration and other related fields.

Citation Information

Patent Citations

  • Method for purifying brackish water through modified aerogel

    CN118387965A

  • Brackish water two-stage nanofiltration device

    CN220485407U

  • PH / temperature double-sensitive interpenetrating network hydrogel and preparation method thereof

    CN113185718A

  • Polyamide hydrogel adsorption material and preparation method thereof

    CN115850571A

  • Hydroximic acid grafted gelatin / polyacrylamide double-network hydrogel adsorbent as well as preparation method and application thereof

    CN117753388A